2015
DOI: 10.1371/journal.pone.0122302
|View full text |Cite
|
Sign up to set email alerts
|

Association between P16INK4a Promoter Methylation and HNSCC: A Meta-Analysis of 21 Published Studies

Abstract: BackgroundThe p16INK4a is an important tumor suppressor gene (TSG) and aberrant methylation of promoter is known to be a major inactivation mechanism of the tumor suppressor and tumor-related genes. Aberrant TSG methylation was considered an important epigenetic silencing mechanism in the progression of head and neck squamous cell carcinoma (HNSCC). However, some studies have reported differences in the methylation frequencies of P16INK4a promoter between cancer and the corresponding control group. Therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 50 publications
1
12
0
1
Order By: Relevance
“…Other risk factors for HNSCC include epigenetic regulation of gene expression, which may lead to the induction and progression of HNSCC (Bragado et al, 2012;Hakami et al, 2014). Increasing evidence suggests that promoter methylation of tumor-related genes can aggravate the disease in HNSCC (Laytragoon-Lewin et al, 2013;Rettori et al, 2013;Warta et al, 2014;Shi et al, 2015). However, few studies have reported on the prognostic value of promoter methylation in HPV-induced HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Other risk factors for HNSCC include epigenetic regulation of gene expression, which may lead to the induction and progression of HNSCC (Bragado et al, 2012;Hakami et al, 2014). Increasing evidence suggests that promoter methylation of tumor-related genes can aggravate the disease in HNSCC (Laytragoon-Lewin et al, 2013;Rettori et al, 2013;Warta et al, 2014;Shi et al, 2015). However, few studies have reported on the prognostic value of promoter methylation in HPV-induced HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative analyses of available HPV+ TCGA cases revealed specific hypermethylated regions downstream of CDKN2A, which correlated with increased transcription of CDKN2A variant p14 (ARF; [184]). CDKN2A is also frequently methylated (23–67 % of cases; [91]) to silence expression of this tumor suppressor [88, 90, 186]; although, degree of methylation and expression changes can vary significantly among individual tumors [187]. The mechanistic and clinical ramifications of this observation are not yet understood.…”
Section: Introductionmentioning
confidence: 99%
“…For most of the methylomics driven studies of HNSCC [183, 185, 188, 189], few cases were analyzed (particularly for HPV+ cases) and additional work is needed to better understanding and interpret the various methylation patterns. How methylomics data is going to be integrated into clinical practice for HNSCC remains to be seen, although prognostic and diagnostic potential of such information is apparent in some cancer types [181, 185, 190].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent meta-analysis from six eligible studies, including 261 patients, Hu et al found that p16 INK4a promoter hypermethylation is correlated with an increased risk of endometrial carcinoma [ 33 ]. Similarly, our earlier meta-analysis reported a significant hypermethylation of p16 INK4a promoter in head and neck squamous cell carcinoma (HNSCC) [ 34 ].…”
Section: Discussionmentioning
confidence: 82%